2012
DOI: 10.1103/physrevb.86.094301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of coherent acoustic phonons and magnons in an antiferromagnet NiO

Abstract: Ultrafast lattice and spin dynamics in an antiferromagnet NiO were studied via reflection and transmission experiments using polarization spectroscopy along with the pump-probe technique. The damped oscillations observed in the reflection experiment are not of spin origin but can be attributed to an interference effect caused by the probe pulse reflected by a propagating wave packet of acoustic phonons. Terahertz oscillations of coherent magnons were observed in the transmission experiment. Three antiferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Measuring transient MLB allows us to detect simultaneously both the transversal and the longitudinal dynamics of L, due to the contributions to the dielectric permittivity tensor proportional to L z L y and L 2 z , assuming L directed along theẑ axis. In contrast, in earlier investigations of laser-induced spin dynamics in compensated antiferromagnets [6,7,25], the transient magneto-optical Faraday rotation was measured. Since in the ground state the magnetization is zero, the Faraday rotation vanishes.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Measuring transient MLB allows us to detect simultaneously both the transversal and the longitudinal dynamics of L, due to the contributions to the dielectric permittivity tensor proportional to L z L y and L 2 z , assuming L directed along theẑ axis. In contrast, in earlier investigations of laser-induced spin dynamics in compensated antiferromagnets [6,7,25], the transient magneto-optical Faraday rotation was measured. Since in the ground state the magnetization is zero, the Faraday rotation vanishes.…”
mentioning
confidence: 78%
“…We can draw this conclusion because, contrary to Refs. [6,7,25], we monitored simultaneously both the transversal and the longitudinal spin dynamics by measuring variations of MLB. Given the nonresonant nature of the coupling between light and spins in the ISRS process, the frequency range of the excitations accessible with this technique is intrinsically much broader.…”
mentioning
confidence: 99%
“…Here we also assume that the temperature changes have no direct effect on . Values of ∂n/∂η 33 = 0 have previously been observed in NiO films as well as in (001)-cut bulk NiO using reflectivity and ellipticity measurements [11,12]. A modulation of the linear refractive index already implies possible consequences for the SHG response arising from changes in the SHG coherence length.…”
Section: Modeling the Shg Response To Optical Excitation Of A Spatmentioning
confidence: 85%
“…For NiO in particular, Bosco et al [11] observed oscillations in time resolved linear reflectivity measurements and Takahara et al [12] recently remarked at the close resemblance between frequencies of these coherent oscillations and the higher-frequency oscillations reported for the SHG response. Dynamics attributed to coherent acoustic phonons have also been observed in the SHG response of a Fe/AlGaAs heterostructure [13].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation